Failure analysis of punching in reinforced concrete flat slabs with openings adjacent to the column. (1st March 2019) - Liberati, Elyson A.P.; Marques, Marília G.; Leonel, Edson D.; Almeida, Luiz C.; Trautwein, Leandro M.
Highlights: The variable investigated is amount of openings adjacent to the column. The energy dissipation capacities of RC slabs with openings considerably decreased. The test results were compared with current design codes. Abstract: One of the main collapse modes of reinforced concrete flat slabs is the punching of the slab-column connection in which the load is applied in a reduced area. Such condition generates significant shear stresses in the slab region around the column. This failure mode should be avoided in order to provide conditions for the development of reinforcements yielding and bending collapse mechanisms prior to the occurrence of shear failure. Then, brittle failure and progressive collapse are prevented. In this study, 12 flat reinforced concrete slabs with dimensions 1800 mm × 1800 mm × 130 mm without shear reinforcement subjected to symmetrical loading were analysed experimentally. These slabs were divided into three groups according to the amount of openings adjacent to the column. The collapse load values and the failure modes were analysed. The results obtained experimentally were compared with results available in the literature, as well as with responses predicted from the normative instructions.